2021
DOI: 10.1002/smll.202101954
|View full text |Cite
|
Sign up to set email alerts
|

Embedding of Ti3C2TxNanocrystals in MAPbI3Microwires for Improved Responsivity and Detectivity of Photodetector

Abstract: Organic–inorganic hybrid MAPbI3 microwires show unique optoelectronic properties for high performances of photodetectors (PDs). However, the defects‐assisted nonradiative recombination is harmful for carrier transport, which limits the performances improvement of MAPbI3 microwires PDs. Traditional organic passivation agents effectively combine the surface defects of microwires and also reduce the mobility of overall film based on the perovskite microwires. Therefore, the improvement of internal carrier transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…In the previous work, we reported that MAPbI 3 MWs could be easily obtained through this synthesis protocol. [18] In the present work, we found that the FAPbI 3 MWs intermediate is more sensitive to the volume ratio of DMF and IPA. As shown in Figure 1b and Figure S1 (Supporting Information), MAPbI 3 MWs intermediate formed immediately in the varied volume ratio of DMF and IPA in a large range (from 1:2 to 1:40), while the FAPbI 3 MWs intermediate only formed quickly in the range from 1:5 to 1:15.…”
Section: Perovskite Mws Synthesissupporting
confidence: 57%
See 2 more Smart Citations
“…In the previous work, we reported that MAPbI 3 MWs could be easily obtained through this synthesis protocol. [18] In the present work, we found that the FAPbI 3 MWs intermediate is more sensitive to the volume ratio of DMF and IPA. As shown in Figure 1b and Figure S1 (Supporting Information), MAPbI 3 MWs intermediate formed immediately in the varied volume ratio of DMF and IPA in a large range (from 1:2 to 1:40), while the FAPbI 3 MWs intermediate only formed quickly in the range from 1:5 to 1:15.…”
Section: Perovskite Mws Synthesissupporting
confidence: 57%
“…Preparation of APbI 3 (A = FA + , MA + , and Cs + ) MWs: MAPbI 3 and FAPbI 3 MWs intermediate was synthesized by a modified process according to previous work. [18] 1 mmol PbI 2 powder (461.01 mg) was added into 1 mL of DMF solvent. Then it was heated to 70 °C and stirred on a hot plate for 30 min to fully dissolve the PbI 2 powder, which was served as solution A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their distinct geometric structures can not only facilitate efficient carrier transport due to the reduced dimensionality, but also tolerate bending along the perpendicular to form flexible and integrated devices. [19][20][21][22][23] Therefore, single-crystal microwires (MWs) are highly desirable for practical applications in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The success of metal halide perovskite materials in the optoelectronic fields of solar cells, [1,2] photodetectors, [3,4] LEDs, [5] lasers [6,7] is often attributed to their excellent photoelectric properties, including high absorption coefficient, tunable bandgap, long exciton diffusion length, low exciton dissociation energy, and high defect tolerating feature. [8][9][10] However, the stateof-the-art perovskite-based devices are vulnerable to thermal and moisture, resulting in inferior stability inevitably.…”
Section: Introductionmentioning
confidence: 99%